(untitled) (Eurasian Journal of Philology Science and Education, 2015)
In 2009, the author discovered the universal law of compatibility of consonants and next following vowel sounds. The law states: consonants and the next following vowel sounds can be combined into syllables, if the articulation of these two sounds is similar and the same. This means that hard consonant sounds can be combined into a syllable with hard vowels only, and soft consonants – with soft vowels only. This scientifically proves that vowels, as well as consonants, in all world languages are palatalized or nonpalatalized. This allowed the author to discover four open soft vowels in Russian and European language: [ä] = [я] = [ә], [ü] = [ю] = [ү] , [ö] = [ё] = [ө], [е].